2011
DOI: 10.1073/pnas.1017300108
|View full text |Cite
|
Sign up to set email alerts
|

Modeling high-grade serous ovarian carcinogenesis from the fallopian tube

Abstract: High-grade serous ovarian carcinoma (HGSOC) is a lethal disease for which improved screening and treatment strategies are urgently needed. Progress in these areas is impeded by our poor understanding of HGSOC pathogenesis. Most ovarian cancer research is based on the hypothesis that HGSOC arises from ovarian surface epithelial cells. However, recent studies suggest that >50% of high-grade serous carcinomas involving the ovary likely arise from fallopian tube epithelium. Therefore, limiting HGSOC research to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
281
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(297 citation statements)
references
References 38 publications
5
281
0
1
Order By: Relevance
“…It is now believed that dissemination of serous cancers may occur by exfoliation of tumor cells originating from the distally located TICs (reviewed in [7]). Recent mouse models have shown transformation of human and mouse fallopian tube tissue into serous cancers through multiple genetic mutations [35,37]. These data suggest that serous cancers may arise from the fallopian tube.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is now believed that dissemination of serous cancers may occur by exfoliation of tumor cells originating from the distally located TICs (reviewed in [7]). Recent mouse models have shown transformation of human and mouse fallopian tube tissue into serous cancers through multiple genetic mutations [35,37]. These data suggest that serous cancers may arise from the fallopian tube.…”
Section: Discussionmentioning
confidence: 94%
“…The FTE is actively being explored as a site of initiation for serous cancers [35][36][37]. Dysplastic lesions identified typically in the distal end of the fallopian tube have been hypothesized to be precursor lesions for invasive serous cancers [38][39][40][41].…”
Section: Ftescs Are Expanded In the Fallopian Tube Epithelium Of Patimentioning
confidence: 99%
“…Embryologically OSE originates from the coelomic epithelium, which also gives rise to the epithelia lining the Fallopian tube, endometrium, cervix, and upper part of vagina. It has recently been advocated that besides OSE, epithelial neoplasms may also arise from the distal part of Fallopian tubes including fimbria (Karst et al 2011) and later get deposited onto the OSE. This should not be of any concern as both OSE and oviductal epithelium have a common origin in coelomic epithelium (Auersperg 2013).…”
Section: Ose Stem Cells and Fshmentioning
confidence: 99%
“…To validate our screening results, we reintroduced GAB2 into HA1E-M cells and found that tumors formed in mice at the same rate (7 of 12, 58%) as that induced by the ovarian cancer oncogene, ID4 (5) (8 of 14, 57%). To determine whether GAB2 expression also transforms immortalized cells relevant to ovarian cancer, we introduced GAB2 into human immortalized ovarian surface epithelial (IOSE) cells expressing the SV40 ER, hTERT, and an activated MEK1-DD allele and immortalized fallopian tube secretory epithelial cells (FTSECs) expressing hTERT and the SV40 large and small T antigens (18). Expression of GAB2 induced significantly larger tumors than control or LACZexpressing control IOSE cells when injected into immunodeficient NOD/IL2Rγ c /SCID mice ( Fig.…”
Section: Gab2 Transforms Immortalized Ovarian and Fallopian Tube-derivedmentioning
confidence: 99%